Modulation of Reactive Oxygen Species Homeostasis as a Pleiotropic Effect of Commonly Used Drugs - Thomas, Carolin; Wurzer, Lia; Malle, Ernst; Ristow, Michael; Madreiter-Sokolowski, Corina T. (Frontiers in Aging, 2022)
Age-associated diseases represent a growing burden for global health systems in our aging society. Consequently, we urgently need innovative strategies to counteract these pathological disturbances. Overwhelming generation of reactive oxygen species (ROS) is associated with age-related damage, leading to cellular dysfunction and, ultimately, diseases. However, low-dose ROS act as crucial signaling molecules and inducers of a vaccination-like response to boost antioxidant defense mechanisms, known as mitohormesis. Consequently, modulation of ROS homeostasis by nutrition, exercise, or pharmacological interventions is critical in aging. Numerous nutrients and approved drugs exhibit pleiotropic effects on ROS homeostasis. In the current review, we provide an overview of drugs affecting ROS generation and ROS detoxification and evaluate the potential of these effects to counteract the development and progression of age-related diseases. In case of inflammation-related dysfunctions, cardiovascular- and neurodegenerative diseases, it might be essential to strengthen antioxidant defense mechanisms in advance by low ROS level rises to boost the individual ROS defense mechanisms. In contrast, induction of overwhelming ROS production might be helpful to fight pathogens and kill cancer cells. While we outline the potential of ROS manipulation to counteract age-related dysfunction and diseases, we also raise the question about the proper intervention time and dosage.